“Ikwekwe yinja1 (a Boy is a Dog)”: Re-humanizing Children and Childhoods in Matthew 2:1-3 & 16-18 in Light of the Boy-child Debate in South Africa (The Thinker, 2024)
In contemporary society, the status of children as fully human is often contested and/or not accepted. The idea that children are not fully human has resulted in a plethora of abuses, including the denial of children’s rights, voices, and agency both in biblical texts and in contemporary society. Notwithstanding, scholars like Marcia Bunge acknowledge that in the Judeo-Christian bible “infants and children are also whole and complete human beings made in the image of God” (2012:65). Many times, the ways in which children are treated in biblical texts (in so far as adults make decisions without their (children) approval, e.g., Abraham’s decision to sacrifice Isaac, Jephthah’s decision to kill her daughter in honour of his agreement with Yahweh, the killing of the boy children during the time of Pharoah and King Herod exhibit the idea that children are not fully human. Since Christians rely on the Bible for inspiration and conduct in both private and public life, it is necessary to study the ways in which children were treated in biblical times. Until recently, biblical scholars did not have much of a deliberate focus on studying children and how they are treated in the Bible.